Health knowledge of fourth year U.P. High School students, 1964-1965 - Limcaco, Priscilla G. 1942- (s.n.], 1966)
This study identified the specific topics and major health areas of health knowledge about which students are most informed and least informed. The author hopes that by using the results of this study, the health education teacher of the UP High School will understand the weaknesses and strengths of students in health information.